The challenge of screening SARS-CoV-2 variants of concern with RT-qPCR: One variant can hide another - Blairon, Laurent (J Virol Methods, 2021)
INTRODUCTION: Following the emergence of SARS-CoV-2 variants of concern (VOCs) worldwide, it is important to monitor local epidemiology to better understand the occurrence of clusters, reinfections, or infection after vaccination. Detecting mutations by specific RT-qPCR is a rapid and affordable alternative to sequencing. However, care must be taken to ensure that the techniques used are up-to-date and adapted to the variants circulating in the studied population. MATERIAL AND METHODS: All samples tested positive for SARS-CoV-2 were screened for detection of mutations of the spike protein using the Novaplex™ SARS-CoV-2 Variants I Assay from week 11 of 2021. Target sought were deletion H69/V70 and mutations N501Y and E484K. From week 18 we used in addition the new Novaplex™ SARS-CoV-2 Variants II Assay for samples with no targets found with the Variants I assay or with the mutation E484K alone, in order to screen the mutations L452R, K417N/T and W152C. RESULTS: Between weeks 11 and 25, 2239 positive samples out of 54,317 were tested with the Variants I Assay. Between weeks 18 and 25, 94 samples met the criteria for being tested with the Variants II Assay. Of these, 47 had the L452R mutation without the W152C mutation, typical in the B.1.617 variant. At week 25, this profile was found in 45.5 % of the samples and was the most frequent. CONCLUSION: According to our observations, variant B.1.617 has become predominant in our institution and most probably in our region. In the absence of the use of the Variants II Assay, they would have been considered wild.